Radiographic and Histopathologic Features in Sarcoidosis: A Pictorial Display - Shaikh, Faisal; Abtin, Fereidoun G.; Lau, Ryan; Saggar, Rajan; Belperio, John A.; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2020)
Sarcoidosis is a multisystemic granulomatous disorder that can affect virtually any organ. However, pulmonary and thoracic lymph node involvement predominates; abnormalities on chest radiographs are present in 80 to 90% of patients with sarcoidosis. High-resolution computed tomographic (HRCT) scans are superior to chest X-rays in assessing extent of disease, and some CT features may discriminate an active inflammatory component (which may be amenable to therapy) from fibrosis (for which therapy is not indicated). Typical findings on HRCT include micronodules, perilymphatic and bronchocentric distribution, perihilar opacities, and varying degrees of fibrosis. Less common findings on CT include mass-like or alveolar opacities, miliary opacities, mosaic attenuation, honeycomb cysts, and cavitation. With progressive disease, fibrosis, architectural distortion, upper lobe volume loss with hilar retraction, coarse linear bands, cysts, and bullae may be observed. We discuss the salient CT findings in patients with sarcoidosis (with a major focus on pulmonary features) and present classical radiographic and histopathological images of a few extrapulmonary sites.
Keywords: sarcoidosis; pulmonary; lymphadenopathy; granuloma; high-resolution CT scan; fibrosis